Novel Insights and New Developments Regarding Coagulation Revealed by Studies of the Anti-Factor IXa (Activated Factor IX)/Factor X Bispecific Antibody, Emicizumab. Issue 5 (May 2020) - Yada, Koji; Nogami, Keiji
Abstract : Emicizumab is a humanized anti-FIXa/FX (factor IXa/X) bispecific monoclonal antibody that mimics FVIIIa (activated factor VIII) cofactor function. The hemostatic efficacy of emicizumab has been confirmed in clinical studies of patients with hemophilia A, irrespective of the presence of FVIII inhibitors. Emicizumab differs in some properties from FVIIIa molecule. Emicizumab requires no activation by thrombin and is not inactivated by activated protein C, but emicizumab-mediated coagulation is regulatable and maintains hemostasis. A small amount of FIXa (activated factor IX) is required to initiate emicizumab-mediated hemostasis, whereas tissue factor/FVIIa (activated factor VII)-mediated FXa (activated factor X) and thrombin activation initiates FVIIIa-mediated hemostasis. Fibrin formation, followed by fibrinolysis, appears to be similar between emicizumab- and FVIIIa-mediated hemostasis. These results suggest possible future uses of emicizumab for treating hemorrhagic diseases other than hemophilia A and reveal previously unobservable behaviors of procoagulation and anticoagulation factors in conventional hemostasis. Here, we have reviewed novel insights and new developments regarding coagulation highlighted by emicizumab.